Árangur afnæmismeðferðar á Íslandi 1977-2006 - Sverrir Gauti Ríkarðsson; Yrsa B. Löve; Björn Rúnar Lúðvíksson; Davíð Gíslason (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) INTRODUCTION: The prevelance of allery and asthma has increased rapidly over the last 3 decades and is now estimated that 25-30% of population in Western industrialized countries show symptoms of allergy or asthma. The aim of this study was to reveal the success of allergen immunotherapy (AIT) in Landspitali from 1977-2006. MATERIAL AND METHODS: During the study period a total number of 289 individuals underwent immunotherapy in outpatient clinic of allergy and asthma in Landspítali. A total number of 169 individuals were contacted, of whom 128 (76%) accepted to participate in the study. The evaluation was based on medical records, standardized questionnaire and skin-prick tests. RESULTS: Patients were evaluated on the average of 20 years after finishing treatment. 118 (92%) patients were desensitized to grass pollen, to birch pollen (30%), cat dander (30%) and dust mite (28%). At the time of the study 67% reported to be asymptomatic or with greatly improved allergy symptoms. Males had better response to AIT than women (p=0.04). Participants with positive family history of allergy and/or asthma in first degree relatives also reported better response to AIT (p=0.02). Furthermore, AIT to grass pollen and dust mite seemed to be more effective than AIT to cat dander and birch (p=0.04). AIT was also shown to reduce asthma. CONCLUSION: AIT for 3-5 years provides significant beneficial effect of allergy and asthma symptoms in patients who undergo such therapy. Finally, it s findings support the notion that AIT may reduce the risk of new allergic manifestations. Inngangur: Tíðni ofnæmis hefur farið ört vaxandi á síðastliðnum þremur áratugum og er nú talið að allt að 25-30% íbúa iðnríkjanna sýni einkenni ofnæmis í einhverri mynd. Tilgangur rannsóknarinnar var að varpa ljósi á árangur afnæmismeðferðar yfir 30 ára tímabil á Íslandi. Efniviður og aðferðir: Á rannsóknartímabilinu frá 1977 til 2006 hófu 289 ...